Developing and Investigating New Methods for Alzheimer’s Disease Modeling Using iPSC Derived Co-cultures of Cortical Neurons and Astrocytes - Bengtsson, Niklas (My University, 2022)
Alzheimer’s disease (AD) is the most common cause of dememtia. Models that mimic the human brain and AD pathology, for drug discovery and developing treatments for AD, are needed. One such model is possibly co-cultures of human induced pluripotent stem cells (HiPSC) derived neurons, astrocytes and microglia. In this project, a protocol for differentiating astrocytes from HiSPCs, was implemented. Immunocytochemistry stainings showed that astrocyte markers were expressed more the longer into differentiation and the more mature the astrocytes got. Functional analysis done through live cell calcium imaging on mature astrocytes, showed that 90% of cells responded after stimulation with ATP. It was shown that mature astrocytes could survive in different neuronal medias, where BrainPhys media gave rise to more expression of astrocyte markers. Co-cultures of mature neurons and astrocytes were created to investigate survival and functionality of neurons when cultured together with astrocytes, and alone. Both cells were found to survive together, where neurons and neurite maturation and proliferation seemed to be improved in the co-cultures. Furthermore, synaptic protein expression was found to be higher in neuron and astrocyte co-cultures compared to neuron mono-cultures and total neurite lengths per cell were slightly improved in co-cultures cultured in neural maintenance media. In a future perspective, the possibility to differentiate astrocytes from HiPSCs may give rise to models, for example co-cultures of neurons, astrocytes and microglia, that mimics the human AD pathology better than models that have been used so far.